Evaluation of the physicochemical and microbiological quality of a gelled formulation made with collagen based on fish scales - Palomino Huarcaya , Roger Alberto (2025)
Objective: The objective of this study was to demonstrate whether a gel formulation developed with collagen extracted from fish scales is stable, functional, and safe for cosmetic applications. Material and Methods: A gel formulation derived from fish scales was developed, and physicochemical parameters (pH, viscosity, protein, lipid, carbohydrate, ash, and moisture content) were analyzed following AOAC (Association of Official Analytical Chemists) methods. Additionally, microbiological aspects (mesophilic bacteria, coliforms, molds, yeasts, and Salmonella spp.) were evaluated, and a sensory test was conducted with consumers. Results: The results showed a pH of 6.8 and a viscosity of 150 cP, which are suitable for stability. Protein content was 25%, carbohydrates reached 60.2%, and lipids were 5.5%. No Salmonella spp. was detected, and other microbiological parameters remained within permissible limits. In the sensory test, the attributes of odor and texture were highly accepted, although the visual appearance received a moderately positive rating. Conclusions: The formulation meets quality standards and represents a functional, safe, and sustainable alternative. Furthermore, its production contributes to the valorization of fishing waste, fostering economic development in coastal areas through a circular economy strategy.